Programmable Control of Two‐Phase Fluid Interface Relative Motion in Electrowetting Device (Adv. Mater. Interfaces 21/2021). Issue 21 (10th November 2021) - Guo, Yuanyuan; Zhuang, Lei; Feng, Hao; Zhong, Benpeng; Henzen, Alex; Groenewold, Jan; Liu, Feilong; Deng, Yong; Tang, Biao; Zhou, Guofu
Abstract : Dynamic Control of Two‐Phase Fluid Interface In article number 2101086, Yuanyuan Guo, Guofu Zhou, and co‐workers demonstrate the inkjet‐printed conductive micropillars (CMPs) on the hydrophobic surface can be used to manipulate the dynamic motion of the oil‐water interface in an electrowetting device. The oil film rupture position, contract direction and rupture voltage can be precisely controlled by varying the position and height of CMPs in the confined structure.